Early sport specialization is associated with increased chance of injury - McCall, K.; Brown, V.; Medina McKeon, J. M. (Journal of Athletic Training, 2019)
Context: Sport specialization for youth athletes is occurring earlier compared with previous generations, increasing the risk of associated physical, mental, and social ramifi cations. We assessed the impact of level of sports specialization on risk of injury. Secondarily, we evaluated the effect of sex on level of sport specialization. Methods: We searched PubMed and SPORTDiscus through September 2018. Search terms included iterations of "sport specialization", "female", "training", "competition", and "injury". Studies were limited to peer-reviewed original articles, published in English within the past 5 years. Selection criteria required studies 1) evaluated sport specialization in youth athletes; and 2) included frequencies of injured and non-injured athletes. Selected outcomes were 1) sport participation numbers; 2) sport specialization classifi cation (low, moderate, high); 3) injury frequencies; and 4) sex of injured athletes. Sport specialization classifi cation was performed utilizing validated or unvalidated scales, with questions regarding 1) the athlete`s ability to identify a "primary sport"; 2) participation in a "single sport only"; 3) the athlete`s need to "quit one sport to focus on primary sport"; and/or 4) "participation >8 months of the year" in a single sport. Odds ratios(OR) [95% CIs] were calculated to determine the association of 1) sport specialization (low v. moderate, low v. high) on injury (injury v. no injury) and 2) sex (female v. male) on sport specialization (low v. moderate, low v. high). Four summary models were calculated to determine pooled effects across studies.An 8-question critical appraisal tool for cohort & case-control studies was used to assess evidence quality. Results: Seven studies were eligible (6 case-control, 1 cohort). Two studies were subsequently removed as they utilized the same datasets as 2 of the already included studies.When compared to low specialized athletes, moderately specialized athletes were 50% more likely to be injured (OR=1.5[1.3, 1.8], p<.001) and highly specialized athletes were 80% more likely to be injured (OR=1.8[1.5, 2.1), p<.001). When compared to males, females were more strongly associated with moderate specialization (OR=1.2[1.1, 1.4], p=0.01) and high specialization (OR=1.5[1.1, 2.0], p=0.01). Included studies each scored 7/8. All studies failed to blind participants or assessors. Conclusions: Early sport specialization has a biopsychosocial impact on young athletes. Based on the included studies, there was a strong association between sport specialization and injury, specifi cally for LE and overuse injuries. Further, female athletes were more likely to be more highly specialized in a sport compared to males. Physically, early sport specialization appears to be an injury risk factor for both sexes. Psychosocially, the rationale for increased sport specialization in female athletes needs further exploration, including a determination of its full impact on injury rates. The clinical magnitude of sport specialization on young athletes has an impact on how ATs can better educate young athletes, parents, and coaches.